Comparison of Postpartum Exercises and Consumption of Purple Sweet Potato Leaves on Reduction of Uterine Fundamental Height in Postpartum Women - Fatiyani Alyensi; Yeni Aryani; Ari Susanti (Postgraduate, University of Mataram, 2023)
The bleeding after childbirth is caused 50 - 60%by weakness or absence of uterine contractions. It is important to provide postpartum services for mothers as one of the main pillars in the strategy to reduce the Maternal Mortality Rate (MMR). Postpartum exercise and administering decoction of purple sweet potato leaves are non-pharmacological techniques that can accelerate uterine involution. This study aims to determine the comparison of postpartum exercise and giving purple sweet potato leaves to reduce uterine fundal height in postpartum women at the Taman Sari Clinic, Pekanbaru City in 2023. This research is quantitative with a quasi-experimental design using one control group and one experimental group with the two method. The number of samples for this study was 20 people per group. Data collection method using observation method. The test used is the Independent T test with a significance level of 95%. The research results showed that the difference in TFU reduction after giving purple sweet potato leaves to postpartum mothers was 8.85 cm. The difference in TFU reduction after postpartum exercise was 10.4 cm. This shows that there is a difference between postpartum exercise and purple sweet potato in reducing TFU in postpartum women with a value of p=0.006. It is hoped that decoction of purple sweet potato leaves can reduce TFU in postpartum mothers